2009
DOI: 10.1159/000193147
|View full text |Cite
|
Sign up to set email alerts
|

Plasma B-Type Natriuretic Peptide as a Marker of Myocardial Asynchrony

Abstract: Objectives: Myocardial asynchrony in postinfarction patients with intraventricular conduction defects (IVCD) may influence plasma levels of B-type natriuretic peptide (BNP). The aim of the study is to evaluate asynchrony parameters in postinfarction patients with IVCD and to define the relationship between plasma levels of BNP and echocardiographic parameters of asynchrony. Methods: The study included 158 patients 6 months after myocardial infarction (MI): 126 patients with IVCD and 32 patients without IVCD. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Very limited data exists on patients with IVCD. Patients with myocardial infarction with IVCD had significantly greater interventricular asynchronies and higher BNP levels than post-myocardial infarction patients without IVCD [ 18 ]. In the Multicenter Unsustained Tachycardia Trial (MUSTT), patients with LBBB or IVCD had lower ejection fractions and a higher prevalence of congestive heart failure than those without these abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Very limited data exists on patients with IVCD. Patients with myocardial infarction with IVCD had significantly greater interventricular asynchronies and higher BNP levels than post-myocardial infarction patients without IVCD [ 18 ]. In the Multicenter Unsustained Tachycardia Trial (MUSTT), patients with LBBB or IVCD had lower ejection fractions and a higher prevalence of congestive heart failure than those without these abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,12 BNP was also established as a valuable marker of myocardial asynchrony. 13,14 In recent years, serum BNP levels became useful in monitoring the population of patients with permanent heart stimulation. It was demonstrated that BNP could be of value in screening for heart failure or a prognostic factor of developing heart failure in patients after pacemaker implantation.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the study by Ciuraszkiewicz et al [1] , which showed that plasma levels of B-type natriuretic peptide 6 months after myocardial infarction (MI) depend on both parameters of left ventricle (LV) function and LV asynchrony. The results suggested that B-type natriuretic peptide may serve as a marker of the LV asynchrony in patients with intraventricular conduction defects (IVCD) and preserved LV systolic function.…”
mentioning
confidence: 99%